SPE Annual Technical Conference and Exhibition 1997
DOI: 10.2118/38889-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Streamline-Based 3D Field-Scale Compositional Reservoir Simulator

Abstract: This paper presents the extension of the streamline approach to full-field, three-dimensional (3D) compositional simulation. The streamline technique decomposes a heterogeneous 3D domain into a number of one-dimensional (1D) streamlines along which all fluid flow calculations are done. Streamlines represent a natural, dynamically changing grid for modeling fluid flow. We use a 1D compositional finite-difference simulator to move components numerically along streamlines, and then map the 1D solutions back onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…Previous studies have shown that streamline methods can predict the global sweep of water floods in heterogeneous reservoirs effectively (see, for example, Thiele and Batycky (2006)). A preliminary extension of streamline methods to compositional simulation was discussed in Thiele et al (1997). Commercial streamline simulators are currently being extended to handle compositional processes, but are not yet at the stage where they can reliably predict performance of (near-) miscible gas injection processes.…”
Section: Existing Solversmentioning
confidence: 99%
“…Previous studies have shown that streamline methods can predict the global sweep of water floods in heterogeneous reservoirs effectively (see, for example, Thiele and Batycky (2006)). A preliminary extension of streamline methods to compositional simulation was discussed in Thiele et al (1997). Commercial streamline simulators are currently being extended to handle compositional processes, but are not yet at the stage where they can reliably predict performance of (near-) miscible gas injection processes.…”
Section: Existing Solversmentioning
confidence: 99%
“…However, infill drilling and large changes in production/injection rates meant that streamtube geometry changed resulting in limitations with this technique. Streamline technology is now practical in many field cases because it includes: Streamline technology includes gravity effects and allows well rate changes (starting/stopping of wells) (7)(8)(9)(10)(11) . This allows engineers to perform a one-step process that evaluates both vertical and areal sweep, and also accounts for well changes.…”
Section: Streamline Based Flow Simulationmentioning
confidence: 99%
“…A streamline simulation method is then less sensitive to grid size and orientation. It has experienced a fast growth particularly in the recent decade (Pollock 1988;Bratvedt et al 1992;King et al 1993;Datta-Gupta and King 1995;Bratvedt et al 1996;Batycky et al 1997;Blunt et al 1996;Thiele et al 1996;Thiele et al 1997;Christie and Clifford 1997;King and Datta-Gupta 1998;Ingebrigtsen et al 1999 Donato and Blunt 2004;Cheng et al 2006). In particular, Batycky et al (1997) gave the history of streamline technical development; a streamline technical review was presented in the papers by Datta-Gupta (1998), Datta-Gupta (2000), and Thiele (2001); Di Donato and Blunt (2004) studied streamline simulation in a dual-porosity model; and Cheng et al (2006) provided streamline simulation in compressible fluids.…”
Section: Introductionmentioning
confidence: 99%